2008
DOI: 10.1097/01.prs.0000293867.05857.90
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine in Aesthetic Facial Surgery: Improving Anesthetic Safety and Efficacy

Abstract: Dexmedetomidine lowered blood pressure, decreased the frequency of oxygen desaturations, and reduced narcotic, anxiolytic, and antiemetic use. When compared with conventional sedation, dexmedetomidine appears to improve anesthetic safety and efficacy for rhytidectomy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 41 publications
1
41
0
2
Order By: Relevance
“…In accordance with Gurbet et al [16] who stated that intraoperative infusion of dexmedetomidine reduces perioperative analgesic requirements. Also the analgesic effects of dexmedetomidine had been appreciated in various setting and various populations [17][18][19]. Our results showed that the sensory block was significantly prolonged in the dexmedetomidine group in comparison to the control group, which confirm that the intrathecal doses of dexmedetomidine used in our study prolonged the sensory block.…”
Section: Discussionsupporting
confidence: 79%
“…In accordance with Gurbet et al [16] who stated that intraoperative infusion of dexmedetomidine reduces perioperative analgesic requirements. Also the analgesic effects of dexmedetomidine had been appreciated in various setting and various populations [17][18][19]. Our results showed that the sensory block was significantly prolonged in the dexmedetomidine group in comparison to the control group, which confirm that the intrathecal doses of dexmedetomidine used in our study prolonged the sensory block.…”
Section: Discussionsupporting
confidence: 79%
“…Walker et al [23] found that no respiratory depression associated with the use of dexmedetomidine had occurred. Taghinia et al [24] also reported that dexmedetomidine decreases the frequency of oxygen desaturation and reduces the amounts of narcotic and anxiolytic requirement. In this study, we did not observe any respiratory depression, hypoxia, or apnoea in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 2 patients (6.66%) experienced nausea, but none had vomiting. Taghinia et al [24] have reported that dexmedetomidine use is associated with decreased use of antiemetics.…”
Section: Discussionmentioning
confidence: 99%
“…Uyanık karotis endarterektomisi sırasında, servikal pleksus bloğu altında, deksmedetomidin ile sedatize edilen hastaların intraoperatif analjezik gereksinimlerinin midazolam ve fentanil kullanılan gruptan daha az olduğu belirtilmiştir (18). Benzer şekilde, yüze uygulanan plastik cerrahi girişimlerinde sedasyon için deksmedetomidin alan hastalarda, geleneksel sedatif ajanlarla kıyaslandığında daha az intraoperatif narkotik ve midazolam ihtiyacı ortaya çıkmıştır (19).…”
Section: Discussionunclassified
“…Propofol ile karşılaştırıldığında, deksmedetomidin ile sağlanan sedasyonun, çocuk ve erişkinlerde arter oksijen satürasyonunu daha iyi koruduğu gözlenmiştir (19,22).…”
Section: Discussionunclassified